IN VITRO MICROPROPAGATION OF DATURA METEL L. THROUGH CALLUS INDUCTION FROM LEAF AND ANTHER CULTURE - MAHAKANT JHA; RAMESH KUMAR PANDEY (The Bioscan, 2012)
The present study was carried out to analyse the effects of growth regulators on Callus formation of Datura metel L. in different explants. Datura metel was cultured in MS medium supplemented with different concentration of 2-4 D, NAA, Kinetin, BAP and IAA (from 1mg/L to 5 mg/L). Medium supplemented with various phytohormone for callus and shoot regeneration. Culture was kept on 25±2 degree temperature and 16h photoperiod while callus was observed on different concentration of auxin or cytokinin alone or in combinations. Most suitable medium for callus induction from leaf and anther were 2-4D (1.5mg/L) in alone and 2-4 D (1.5mg/L) + Kinetin (2mg/L) + IAA (1mg/L) in combinations.